Analisis Bentuk Dan Struktur Lagu Cinta Sejati Ciptaan Melly Goeslaw - Egi Winovla Erman; Yensharti Yensharti (SENDRATASIK UNP, 2021)
This research discusses the Analysis of The Form and Structure of Melly Goeslaw's True Love Song which deals with motif processing, phrase processing, and period processing. This research includes qualitative research with content analysis approach that is systematic, objectivity, and generalization. This research data is collected from library study activities, observations, and labor work. Data analysis is done by means of data reduction, analysis and conclusion.  Based on the analysis of the song True Love created by Melly Goeslaw found The Shape of The Song is 4 parts with the sentences A A' B C and D in detail with the arrangement of sentences A (a, a1), A' (a2, b), B (c, c1), B (c, c1), C (d, d1), and D (c2, c4). Judging from the structure of the song is formed from 20 motifs. The processing of motifs from one basic or initial motif is developed by processing in a ha-rafiah, sequen up and down sequen, interval magnification and in-terval downsizing. The motives are m, m1, m2, m3, m4, n, o, p, q, q1, r, r1, r2, r3, s, s1, h, i, i1, and j. From the motive formed antecedent phrases, consequent phrases and connecting phrases as many as 15 phrases namely a, a1, a2, b, c (rep 1x), c1 (repetition 1x), c2, c3, d, d1 and phrase p / liaison (rep 2x). The end of period A has half kadens, the end of period A' has half kadens, the end of period B and D has perfect authentic cadence and the end of periodC has deceptive cadence. The D-shape is the part that modulates from the base tone of F Major to G Major.